The Urgency of Transformation of Islamic Education in the Era of Technology Disruption in the Post-Millennial Muslim Generation - Rahman Rasyidi; Fauzi Fauzi (Budapest International Research and Critics University, 2022)
The rapid development of information technology affects the world of education, including Islamic education. The responsibility of Islamic education in guiding humans in the face of the post-millennial era is an important thing to research. This study aims to identify the characteristics of the post-millennial Muslim generation in the future. Based on the literature study method, this study found that the post-millennial Muslim generation has different features from the previous generation. Based on these findings, it is urgent to transform Islamic education in the era of technological disruption in the post-millennial Muslim age.